2016
DOI: 10.1111/odi.12541
|View full text |Cite
|
Sign up to set email alerts
|

Nystatin and miconazole: pharmacological and clinical evidence regarding interactions with warfarin

Abstract: Miconazole and nystatin used as topical antifungal drugs do not interact equally strongly with warfarin. Miconazole oral gel can clearly interact with warfarin to cause derangement of anticoagulation. Nystatin appears unlikely to interact with warfarin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 42 publications
1
3
1
Order By: Relevance
“…However, the data collection is insufficiently described, and the authors did not provide any potential mechanism to support the reported effect of nystatin on warfarin's anticoagulant activity . Overall, their findings are unlikely to reflect a representative sampling of the clinical population at risk, and contrast with the findings of the present study as well as a recent literature review and analysis of UK adverse drug reaction surveillance reports finding no evidence of a DDI between nystatin and warfarin .…”
Section: Discussioncontrasting
confidence: 94%
See 2 more Smart Citations
“…However, the data collection is insufficiently described, and the authors did not provide any potential mechanism to support the reported effect of nystatin on warfarin's anticoagulant activity . Overall, their findings are unlikely to reflect a representative sampling of the clinical population at risk, and contrast with the findings of the present study as well as a recent literature review and analysis of UK adverse drug reaction surveillance reports finding no evidence of a DDI between nystatin and warfarin .…”
Section: Discussioncontrasting
confidence: 94%
“…Our findings of increased INR values in warfarin users after co‐prescription of miconazole oral gel are in line with multiple case reports , a recent case series and pharmacokinetic data . Overall, current evidence thus supports the presence of a clinically relevant DDI between warfarin and topical miconazole .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…4 Numerous reports of miconazole oral gel and warfarin interactions are succinctly described by Pemberton. 5 Miconazole-warfarin interactions have also been reported with topical use of miconazole on the cutaneous surface and the vaginal mucosa [Table 1]. Devaraj et al have described an alarming rise in international normalized ratio from a range of '2.2 and 3.1' to 21.4 in an 80-year-old man on long-term warfarin, following topical miconazole application for 2 weeks on the groins.…”
Section: Beware Of Miconazole -Warfarin Interactions!mentioning
confidence: 99%
“…Instead, Nystatin is considered the first-line medication for treating uncomplicated oral candidiasis [ 1 ]. Each 1 mL of Nystatin oral suspension contains 100,000 International Units (IU) of Nystatin and the following components: sodium carboxymethylcellulose, methyl p-hydroxybenzoate (E218), propyl p-hydroxybenzoate (E216), sodium metabisulphite (E223), sucrose, saccharin sodium, sodium citrate, permaseal aniseed flavor, and purified water [ 22 ]. The recommended dose of Nystatin ranges from 100,000 to 200,000 IU, four times/day for newborns/infants, and 200,000 to 600,000 IU, four times/day for children and adults [ 23 ].…”
Section: Introductionmentioning
confidence: 99%